Doctors on film. (16th December 2022) - Smith, Anna
Abstract : Medicine is surprisingly under-represented in the world of cinema, considering how intensely emotional and gripping the life and death dramas of the practice can be. The leading film critic Anna Smith discusses the films that have impressed on her the plight of patients and physicians, while our BMJ columnists (and editor) have their say